2003
DOI: 10.1103/physrevlett.90.014103
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Scaling in the Decoherent Quantum-Classical Transition for Chaotic Systems

Abstract: The quantum to classical transition has been shown to depend on a number of parameters. Key among these are a scale length for the action,h, a measure of the coupling between a system and its environment, D, and, for chaotic systems, the classical Lyapunov exponent, λ. We propose computing a measure, reflecting the proximity of quantum and classical evolutions, as a multivariate function of (h, λ, D) and searching for transformations that collapse this hyper-surface into a function of a composite parameter ζ =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 14 publications
6
41
0
Order By: Relevance
“…However that extrapolated limit is substantially smaller than the typical statistical errors for ensemble sizes of 1,000,000 to 2,000,000, and so is not significantly The maximum value of |qm − cl| 1 for the quantum and classical probability distributions must depend on the three parameters β, σ, and τ c . However, in agreement with arguments presented by Pattanayak et al [17], the data was found to collapse onto a single curve parameterized by ξ = β 2 /D (Fig. 23).…”
Section: A Environmental Effects In the Saturation Regimesupporting
confidence: 90%
“…However that extrapolated limit is substantially smaller than the typical statistical errors for ensemble sizes of 1,000,000 to 2,000,000, and so is not significantly The maximum value of |qm − cl| 1 for the quantum and classical probability distributions must depend on the three parameters β, σ, and τ c . However, in agreement with arguments presented by Pattanayak et al [17], the data was found to collapse onto a single curve parameterized by ξ = β 2 /D (Fig. 23).…”
Section: A Environmental Effects In the Saturation Regimesupporting
confidence: 90%
“…1, we quantify the correlation between any two quantities f (θ, φ) and g(θ, φ) as a generalized Kullback-Liebler distance [14]. Here Tr denotes the trace or double integral over the variables (θ, φ).…”
Section: B Comparison Of Correlationsmentioning
confidence: 99%
“…For a classically chaotic, one-dimensional, time-dependent Hamiltonian, it was found that the interaction with a large (Markovian) environment would transform the dynamics of the Wigner function into that of the classical phase-space density, at least under some circumstances [19]. The study of the quantum-to-classical transition for phasespace densities under generic environmental interactions is often referred to as "decoherence" [20,21]. Heuristic arguments were devised to explain this phenomenon for classically chaotic systems [20] although, due to the complexity of the quantum and classical evolution equations for these systems, such arguments are not easy to make precise.…”
Section: Introductionmentioning
confidence: 99%